2021
DOI: 10.18632/aging.203240
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LINC00665 suppresses the progression of lung adenocarcinoma via regulating miR-181c-5p/ZIC2 axis

Abstract: Long non-coding RNA (lncRNA) LINC00665 was demonstrated to be upregulated in lung adenocarcinoma (LUAD) and target miR-181c-5p. ZIC2, which is upregulated in LUAD, serves as a putative target of miR-181c-5p. In this study, we aimed to reveal whether LINC00665 regulates miR-181c-5p/ZIC2 axis to promote LUAD progression. The results showed that LINC00665, HOXA1, ZIC2, and HOXA11 levels were increased in LUAD tissues, while miR-181c-5p level was decreased when compared to the adjacent normal tissues. High express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…If the disease is not controlled in time, the condition deteriorates rapidly, and the tumor occupies most of the lungs, which will have a great impact on the patient's breathing and pose a great threat to the patient's life [1][2][3][4]. Isolated lung adenocarcinoma is a special type of lung adenocarcinoma, which only manifests as an isolated pulmonary nodule and is prone to occult lymph nodes metastasis, leading to missed diagnosis and misdiagnosis, delaying the best treatment opportunity, and endangering the patient's life [5,6]. At present, an X-ray plain film is the main imaging method for screening and diagnosing chest diseases, but this technology is affected by overlapping, and the resolution is relatively poor [7].…”
Section: Introductionmentioning
confidence: 99%
“…If the disease is not controlled in time, the condition deteriorates rapidly, and the tumor occupies most of the lungs, which will have a great impact on the patient's breathing and pose a great threat to the patient's life [1][2][3][4]. Isolated lung adenocarcinoma is a special type of lung adenocarcinoma, which only manifests as an isolated pulmonary nodule and is prone to occult lymph nodes metastasis, leading to missed diagnosis and misdiagnosis, delaying the best treatment opportunity, and endangering the patient's life [5,6]. At present, an X-ray plain film is the main imaging method for screening and diagnosing chest diseases, but this technology is affected by overlapping, and the resolution is relatively poor [7].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, they revealed that LINC00665 upregulated E2F3 expression by acting as a competing endogenous RNA (ceRNA) for miR-138-5p, thereby promoting lung cancer progression ( Wang et al, 2020b ). Similarly, Wei et al (2021) concluded that Linc00665 could bind with miR-181c-5p to upregulate ZIC2, thereby promoting the growth and invasion of lung cancer cells. Huang et al (2021) determined that LINC00665/miR-let-7b/CCNA2 was an essential ceRNA network related to the prognosis of lung cancer.…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“…Researchers used FISH and qRT-PCR to investigate the subcellular location of LINC00665, and the results revealed that LINC00665 was predominately located in the cytoplasm ( Wang et al, 2021a ). Researchers performed flow cytometry, CCK-8 assays, and transwell assays to evaluate the effects of LINC00665 on lung cancer cell apoptosis, proliferation, migration, and invasion ( Cong et al, 2019 ; Wang et al, 2020b ; Wang et al, 2021a ; Yang et al, 2021a ; Wei et al, 2021 ). The high expression of linc00665 promoted the proliferation, migration, invasion of lung cancer cells in vitro and modulated cell cycle arrest and apoptosis ( Cong et al, 2019 ; Wang et al, 2020b ; Wang et al, 2021a ; Yang et al, 2021a ; Wei et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings that LINC00665 was primarily distributed in the cytoplasm of NSCLC cells, LINC00665 was found to recruit EZH2 to the CDKN1C promoter region to facilitate the demethylation of histone H3K27 and inhibit CDKN1C transcription. As a ceRNA, LINC00665 could regulate the expression of E2F3, AKR1B10, ZIC2, MYCBP, and CCNA2 by sponging miR-138-5p ( 40 ), miR-98 ( 41 ), miR-181c-5p ( 42 ), miR-195-5p ( 43 ), and miR-let-7b ( 44 ), respectively. LINC00665 also participated in tumor angiogenesis.…”
Section: Linc00665 Dysregulation and Biological Roles In Human Cancersmentioning
confidence: 99%